Preparation method of blister UV (ultraviolet) coating for PVC (polyvinyl chloride) film photoetching process
By adding sustained release filler and modified diluent to UV coating, the problem of poor coating flexibility during the blistering process of PVC film is solved, and the wear resistance and self-healing properties of the coating are improved, ensuring that the coating does not crack during deformation.
Patent Information
- Application Number
- CN202510627441.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-15
- Publication Date
- 2025-07-18
- Estimated Expiration
- 2045-05-15
AI Technical Summary
During the blistering process of PVC film, existing UV coatings are prone to cracks in the coating, which affects product quality.
The combination of sustained release filler and modified diluent is used to improve the wear resistance and flexibility of the coating film by adding sustained release filler and modified diluent to the coating.
The wear resistance and self-healing properties of the coating film are enhanced, and the coating film cracking or peeling problems caused by deformation of the blister film is avoided.
Smart Images

Figure CN120329856A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of UV coatings, and specifically to a preparation method of a PVC film lithography process-absorbable UV coating. Background Art
[0002] The absorbable UV coating, that is, the ultraviolet light-curable coating that can be heat-formed, has good hand feeling and scratch resistance. Coated on the PVC film material and cured by UV, it can be integrally formed with the composite board by vacuum heat-forming. It can not only be flatly attached, but also be bent and edge-wrapped, and has a wide range of applications.
[0003] By adding particulate fillers to the UV coating, the corrosion resistance and wear resistance of the coating can be improved, but the flexibility of the coating is not good. During the heat-forming process, the coating will deform with the PVC film together, and poor flexibility of the coating is likely to cause cracks, affecting the product quality. Based on this, a preparation method of a PVC film lithography process-absorbable UV coating is proposed. Summary of the Invention
[0004] Aiming at the deficiencies of the prior art, the present invention provides a preparation method of a PVC film lithography process-absorbable UV coating, which improves the wear resistance, self-healing performance and flexibility of the coating film through the combined use of a slow-release filler and a modified diluent.
[0005] To achieve the above object, the present invention provides the following technical solution: A preparation method of a PVC film lithography process-absorbable UV coating, including the following steps,
[0006] (1) Pour the PUA prepolymer and the modified diluent into a high-speed stirrer and mix them evenly;
[0007] (2) Add the slow-release filler and the photoinitiator to the high-speed stirrer and mix them evenly to obtain a mixture;
[0008] (3) After filtering and degassing the mixture, the PVC film lithography process-absorbable UV coating is prepared.
[0009] Preferably, in step (1), the preparation method of the PUA prepolymer is: S1-1. Stir and mix isophorone diisocyanate and dibutyltin dilaurate, then dropwise add castor oil and acetone, keep warm at 50-60 °C for 2-3 h, and then dropwise add hydroxyethyl acrylate, pentaerythritol tetraacrylate and 4-methoxyphenol and continue to react for 3-4 h to obtain a reaction material; S1-2. Perform rotary evaporation on the reaction material to remove acetone to obtain the PUA prepolymer.
[0010] Preferably, in step S1-1, the mass ratio of isophorone diisocyanate, dibutyltin dilaurate, castor oil, 2-hydroxyethyl acrylate, pentaerythritol tetraacrylate, and 4-methoxyphenol is (9-10):(0.1-0.15):(12-15):(5-6):(2-3):(0.05-0.06).
[0011] Preferably, in step S1-1, the material ratio of castor oil to acetone is 1:3 g / mL.
[0012] Preferably, in step (1), the preparation method of the modified diluent is as follows: S2-1, uniformly mix cardanol, 4-(dimethylamino)pyridine, triethylamine, 4-methoxyphenol, and tetrahydrofuran, cool down to 0 °C, stir and add acryloyl chloride, and then react at 40-45 °C for 5-7 h to obtain a premix; S2-2, extract the premix with diethyl ether, wash it with saturated sodium bicarbonate, and wash it with deionized water, take the upper layer solution and dry it with anhydrous magnesium sulfate, and then filter and rotary evaporate to remove diethyl ether to obtain the modified diluent.
[0013] Preferably, in step S2-1, the mass ratio of cardanol, 4-(dimethylamino)pyridine, triethylamine, 4-methoxyphenol, and acryloyl chloride is (28-30):(0.5-0.6):(10-12):(0.10-0.15):(9-10).
[0014] Preferably, in step S2-1, the material ratio of triethylamine to tetrahydrofuran is 1:2 g / mL.
[0015] Preferably, in step (2), the preparation method of the slow-release filler is as follows: pour hollow mesoporous silica microspheres into linseed oil, and ultrasonically treat for 3-5 h; after filtration, dry the surface, and spray with a polyvinyl alcohol solution, and then dry to obtain the slow-release filler.
[0016] Preferably, in step (2), the photoinitiator is selected from photoinitiator 1173.
[0017] The present invention also provides a PVC film lithography process absorbable UV coating, which includes the following raw materials in terms of mass percentage: 60-75% of PUA prepolymer, 15-20% of modified diluent, 10-15% of slow-release filler, and 2-4% of photoinitiator.
[0018] The present invention provides a preparation method of a PVC film lithography process absorbable UV coating, which has the following beneficial effects compared with the prior art:
[0019] The UV coating prepared by the present invention improves the wear resistance, self-healing performance and flexibility of the coating film through the combined use of a slow-release filler and a modified diluent, enabling the coating film to be better applied to the blister film and effectively avoiding the problems of coating film cracking or peeling caused by the deformation of the blister film.
[0020] The present invention prepares a modified diluent by reacting acryloyl chloride with the phenolic hydroxyl group of cardanol and adds it to the coating. The side-chain alkyl fatty chain structure increases the flexibility of the coating film, enabling the coating film to withstand greater deformation without cracking and being well applied to the blister film.
[0021] The present invention coats linseed oil in hollow mesoporous silica microspheres. When cracks occur in the coating film, the polyvinyl alcohol film breaks, causing the internal linseed oil to flow out to the crack and contact with oxygen, and the linolenic acid will crosslink and cure to achieve crack healing. Description of the Drawings
[0022] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The schematic embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation of the present application. In the drawings:
[0023] Figure 1 It is the infrared spectrogram of the PUA prepolymer in Example 2 of the present invention. Detailed Embodiments
[0024] The following examples are used to detail the implementation manners of the present application, so as to fully understand how the present application uses technical means to solve technical problems and achieve the realization process of technical effects and implement accordingly.
[0025] Example 1
[0026] The preparation method of the PUA prepolymer is as follows:
[0027] S1-1. Stir and mix isophorone diisocyanate and dibutyltin dilaurate, then dropwise add castor oil and acetone. After maintaining the temperature at 60 °C for 2 h, dropwise add 2-hydroxyethyl acrylate, pentaerythritol tetraacrylate and 4-methoxyphenol and continue to react for 4 h to obtain a reaction material;
[0028] The mass ratio of the above isophorone diisocyanate, dibutyltin dilaurate, castor oil, 2-hydroxyethyl acrylate, pentaerythritol tetraacrylate and 4-methoxyphenol is 10:0.1:15:5:3:0.05; the material-liquid ratio of castor oil and acetone is 1:3 g / mL.
[0029] S1-2. Perform rotary evaporation on the reaction material to remove acetone and obtain the PUA prepolymer.
[0030] Example 2
[0031] The preparation method of the PUA prepolymer is as follows:
[0032] S1-1. Stir and mix isophorone diisocyanate and dibutyltin dilaurate, then dropwise add castor oil and acetone. After keeping warm at 50 °C for 3 h, dropwise add 2-hydroxyethyl acrylate, pentaerythritol tetraacrylate and 4-methoxyphenol and continue to react for 3 h to obtain a reaction material;
[0033] The mass ratio of the above isophorone diisocyanate, dibutyltin dilaurate, castor oil, 2-hydroxyethyl acrylate, pentaerythritol tetraacrylate and 4-methoxyphenol is 9:0.15:12:6:2:0.06; the material-liquid ratio of castor oil and acetone is 1:3 g / mL.
[0034] S1-2. Carry out rotary evaporation on the reaction material to remove acetone, and obtain the PUA prepolymer.
[0035] Example 3
[0036] The preparation method of the modified diluent is as follows:
[0037] S2-1. Uniformly mix cardanol, 4-(dimethylamino)pyridine, triethylamine, 4-methoxyphenol and tetrahydrofuran. After cooling to 0 °C, stir and add acryloyl chloride, and then react at 45 °C for 5 h to obtain a premixed material;
[0038] The mass ratio of the above cardanol, 4-(dimethylamino)pyridine, triethylamine, 4-methoxyphenol and acryloyl chloride is 30:0.5:12:0.10:10; the material-liquid ratio of triethylamine and tetrahydrofuran is 1:2 g / mL.
[0039] S2-2. Extract the premixed material with ether, wash it with saturated sodium bicarbonate and deionized water in sequence. Take the upper layer solution and dry it with anhydrous magnesium sulfate, and then filter and rotary evaporate to remove ether to obtain the modified diluent.
[0040] Example 4
[0041] The preparation method of the modified diluent is as follows:
[0042] S2-1. Uniformly mix cardanol, 4-(dimethylamino)pyridine, triethylamine, 4-methoxyphenol and tetrahydrofuran. After cooling to 0 °C, stir and add acryloyl chloride, and then react at 40 °C for 7 h to obtain a premixed material;
[0043] The mass ratio of the above-mentioned cardanol, 4-(dimethylamino)pyridine, triethylamine, 4-methoxyphenol and acryloyl chloride is 28:0.6:10:0.15:9; the solid-liquid ratio of triethylamine and tetrahydrofuran is 1:2 g / mL. S2-2, the premix is extracted with ether, washed with saturated sodium bicarbonate and deionized water in sequence, the upper layer solution is taken and dried with anhydrous magnesium sulfate, and then filtered and the ether is removed by rotary evaporation to obtain a modified diluent.
[0044] Example 5
[0045] The method for preparing a UV coating capable of being blistered by a PVC film photolithography process comprises the following steps:
[0046] (1) The following raw materials are prepared in percentage by mass: 68% of PUA prepolymer, 15% of modified diluent, 15% of slow-release filler, and 11732% of photoinitiator;
[0047] The preparation method of the above-mentioned sustained-release filler is as follows: pour hollow mesoporous silica microspheres (particle size is 3-5μm, and the mesopore diameter is above 10nm) into linseed oil and ultrasonically treat for 5h; after filtering, the surface is dried and sprayed with polyvinyl alcohol solution, and after drying, a sustained-release filler is obtained.
[0048] (2) Pour the PUA prepolymer and the modified diluent into a high-speed stirrer and mix them evenly;
[0049] (3) adding the slow-release filler and the photoinitiator 1173 into a high-speed stirrer and uniformly mixing them to obtain a mixture;
[0050] (4) After the mixture is filtered and degassed, a PVC film photolithography-based UV coating is obtained.
[0051] In this embodiment, the PUA prepolymer in Example 1 and the modified diluent in Example 3 are used.
[0052] Example 6
[0053] The method for preparing a UV coating capable of being blistered by a PVC film photolithography process comprises the following steps:
[0054] (1) The following raw materials are prepared in percentage by mass: 66% PUA prepolymer, 20% modified diluent, 10% slow-release filler, and 11734% photoinitiator.
[0055] The preparation method of the above-mentioned sustained-release filler is as follows: pour hollow mesoporous silica microspheres (particle size is 3-5μm, mesopore diameter is above 10nm) into linseed oil and ultrasonically treat for 3h; after filtering, dry the surface and spray it with polyvinyl alcohol solution, and after drying, obtain the sustained-release filler.
[0056] (2) Pour the PUA prepolymer and the modified diluent into a high-speed stirrer and mix them evenly;
[0057] (3) Add the sustained-release filler and photoinitiator 1173 to the high-speed stirrer and mix them evenly to obtain a mixture;
[0058] (4) After the mixture is filtered and degassed, a PVC film lithography process-absorbable UV coating is prepared.
[0059] In this example, the PUA prepolymer in Example 2 and the modified diluent in Example 3 are used.
[0060] Example 7
[0061] A method for preparing a PVC film lithography process-absorbable UV coating includes the following steps:
[0062] (1) Calculate the ingredients by mass percentage: 70% PUA prepolymer, 15% modified diluent, 12% sustained-release filler, 3% photoinitiator 1173.
[0063] The preparation method of the above-mentioned sustained-release filler is as follows: Pour hollow mesoporous silica microspheres (particle size 3-5 μm, mesoporous pore diameter above 10 nm) into linseed oil and perform ultrasonic treatment for 4 h; After filtration, dry the surface, and spray with a polyvinyl alcohol solution, and after drying, the sustained-release filler is obtained.
[0064] (2) Pour the PUA prepolymer and the modified diluent into a high-speed stirrer and mix them evenly;
[0065] (3) Add the sustained-release filler and photoinitiator 1173 to the high-speed stirrer and mix them evenly to obtain a mixture;
[0066] (4) After the mixture is filtered and degassed, a PVC film lithography process-absorbable UV coating is prepared.
[0067] In this example, the PUA prepolymer in Example 2 and the modified diluent in Example 4 are used.
[0068] Comparative Example 1
[0069] A method for preparing a PVC film lithography process-absorbable UV coating includes the following steps:
[0070] (1) Calculate the ingredients by mass percentage: 82% PUA prepolymer, 15% modified diluent, 3% photoinitiator 1173.
[0071] (2) Pour the PUA prepolymer and the modified diluent into a high-speed stirrer and mix them evenly;
[0072] (3) Add photoinitiator 1173 to a high-speed stirrer and mix evenly to obtain a mixed material;
[0073] (4) After the mixed material is filtered and degassed, a PVC film lithography process blisterable UV coating is prepared.
[0074] In this comparative example, the PUA prepolymer in Example 2 and the modified diluent in Example 4 are used.
[0075] Comparative Example 2
[0076] A method for preparing a PVC film lithography process blisterable UV coating includes the following steps:
[0077] (1) Prepare the following raw materials by mass percentage: 70% PUA prepolymer, 15% modified diluent, 12% hollow mesoporous silica microspheres, and 3% photoinitiator 1173.
[0078] (2) Pour the PUA prepolymer and the modified diluent into a high-speed stirrer and mix evenly;
[0079] (3) Add hollow mesoporous silica microspheres (particle size 3 - 5 μm, mesopore diameter above 10 nm) and photoinitiator 1173 to the high-speed stirrer and mix evenly to obtain a mixed material;
[0080] (4) After the mixed material is filtered and degassed, a PVC film lithography process blisterable UV coating is prepared.
[0081] In this comparative example, the PUA prepolymer in Example 2 and the modified diluent in Example 4 are used.
[0082] Comparative Example 3
[0083] A method for preparing a PVC film lithography process blisterable UV coating includes the following steps:
[0084] (1) Prepare the following raw materials by mass percentage: 70% PUA prepolymer, 15% hydroxyethyl methacrylate diluent, 12% slow-release filler, and 3% photoinitiator 1173.
[0085] The preparation method of the above slow-release filler is as follows: Pour hollow mesoporous silica microspheres into linseed oil and perform ultrasonic treatment for 4 h; after filtration, dry the surface, and spray with a polyvinyl alcohol solution, and after drying, obtain the slow-release filler.
[0086] (2) Pour the PUA prepolymer and the hydroxyethyl methacrylate diluent into a high-speed stirrer and mix evenly;
[0087] (3) Add the slow-release filler and photoinitiator 1173 to the high-speed stirrer and mix evenly to obtain a mixed material;
[0088] (4) After the mixture is filtered and degassed, a PVC film lithography process-absorbable UV coating is prepared.
[0089] In this comparative example, the PUA prepolymer in Example 2 is used.
[0090] Quality inspection
[0091] Taking the PVC film lithography process-absorbable UV coatings in Examples 5-7 and Comparative Examples 1-3 as test samples, coating them on thin sheets, and obtaining coating films after photocuring.
[0092] 1. Using a JM-3 type coating abrasion tester to measure, controlling the load amount to be 1×10 4 N until 100 revolutions. The wear resistance calculation formula is as follows: Wear resistance = (mass of the coating sample before wear - mass of the coating sample before wear) / coating thickness. The elongation at break of the coating film is detected according to the standard of GB / T2567-2008. The specific results are shown in the following table.
[0093] Table 1 Wear resistance and elongation at break
[0094] Category Wear resistance (mg / μm) Elongation at break (%) Example 5 3.1 15.0 Example 6 3.0 16.4 Example 7 2.8 15.5 Comparative Example 1 4.6 15.2 Comparative Example 2 3.2 14.9 Comparative Example 3 3.3 10.7
[0095] It can be seen from the above table that: compared with Example 7, no slow-release filler was added in Comparative Example 1, resulting in a significant decrease in the wear resistance of the coating film; compared with Example 7, no modified diluent was used in Comparative Example 3, resulting in poor toughness.
[0096] 2. Scratch self-healing and repeated self-healing: Use a scalpel to make a small scratch on the surface of the coating film, and it will self-heal at room temperature until the small crack disappears. After the scratch self-heals, make a small crack at the same position again, repeat the above operation, and observe whether the crack can continue to self-heal. The specific detection results are shown in the following table.
[0097] Table 2 Self-healing property
[0098] Category Healing condition Number of repeated self-healing times Example 5 Healed 13 Example 6 Healed 12 Example 7 Healed 14 Comparative Example 1 Not healed / Comparative Example 2 Not healed / Comparative Example 3 Healed 13
[0099] It can be seen from the above table that: no slow-release filler was used in Comparative Example 1, so there is no tendency of self-healing, indicating that the use of slow-release filler can indeed endow the coating film with better self-healing performance.
[0100] Although the embodiments of the present invention have been shown and described, for those of ordinary skill in the art, it can be understood that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the present invention. The scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. Preparation method of PVC film lithography process-absorbable UV coating, characterized in that, The following steps are involved: (1) Pour the PUA prepolymer and the modified diluent into a high-speed stirrer and mix them evenly; (2) adding a slow-release filler and a photoinitiator into a high-speed stirrer and uniformly mixing them to obtain a mixture; (3) After the mixture is filtered and degassed, a PVC film photolithography-based UV coating is obtained.
2. The preparation method of the PVC film lithography process-absorbable UV coating according to claim 1, characterized in that, In step (1), the preparation method of the PUA prepolymer is: S1-1, isophorone diisocyanate and dibutyltin dilaurate are stirred and mixed, and then castor oil and acetone are added dropwise, and hydroxyethyl acrylate, pentaerythritol tetraacrylate and 4-methoxyphenol are added dropwise after keeping the temperature at 50-60° C. for 2-3 hours, and the reaction is continued for 3-4 hours to obtain a reaction material; S1-2, removing acetone from the reaction material by rotary evaporation to obtain a PUA prepolymer.
3. The preparation method of the PVC film lithography process-absorbable UV coating according to claim 2, characterized in that, In step S1-1, the mass ratio of isophorone diisocyanate, dibutyltin dilaurate, castor oil, hydroxyethyl acrylate, pentaerythritol tetraacrylate and 4-methoxyphenol is (9-10): (0.1-0.15): (12-15): (5-6): (2-3): (0.05-0.06).
4. The preparation method of the PVC film lithography process-absorbable UV coating according to claim 2, characterized in that, In step S1-1, the material-liquid ratio of castor oil and acetone is 1:3 g / mL.
5. The preparation method of the PVC film lithography process-absorbable UV coating according to claim 1, characterized in that, In step (1), the preparation method of the modified diluent is as follows: S2-1, uniformly mix cardanol, 4-(dimethylamino)pyridine, triethylamine, 4-methoxyphenol and tetrahydrofuran, cool to 0°C, add acryloyl chloride with stirring, and then react at 40-45°C for 5-7h to obtain a premix; S2-2. The premix is extracted with ether, washed with saturated sodium bicarbonate and deionized water in sequence, the upper layer solution is taken and dried with anhydrous magnesium sulfate, and then filtered and the ether is removed by rotary evaporation to obtain a modified diluent.
6. The preparation method of the PVC film lithography process-absorbable UV coating according to claim 5, characterized in that, In step S2-1, the mass ratio of the cardanol, 4-(dimethylamino)pyridine, triethylamine, 4-methoxyphenol and acryloyl chloride is (28-30): (0.5-0.6): (10-12): (0.10-0.15): (9-10).
7. The preparation method of the PVC film lithography process-absorbable UV coating according to claim 1, characterized in that, In step S2-1, the solid-liquid ratio of triethylamine and tetrahydrofuran is 1:2 g / mL.
8. The preparation method of the PVC film lithography process-absorbable UV coating according to claim 1, wherein, In step (2), the preparation method of the sustained-release filler is as follows: pouring hollow mesoporous silica microspheres into linseed oil and ultrasonically treating for 3-5 hours; filtering and drying the surface, spraying with polyvinyl alcohol solution, and drying to obtain a sustained-release filler.
9. The preparation method of the PVC film lithography process-absorbable UV coating according to claim 1, characterized in that, In step (2), the photoinitiator is selected from photoinitiator 1173.
10. The PVC film lithography process absorbable UV coating prepared by the preparation method according to any one of claims 1-9, characterized in that, Calculated by mass percentage, the raw materials include: 60-75% of PUA prepolymer, 15-20% of modified diluent, 10-15% of slow-release filler, and 2-4% of photoinitiator.
Citation Information
Patent Citations
Ultraviolet (UV)-curable paint, coating and graphite heat dissipation material
CN107201163A
Urethane acrylate UV curing resin and preparation method and application thereof
CN117843878A